KOTAK POP-UP BERBASIS PROBLEM SOLVING: PENGEMBANGAN MEDIA PEMBELAJARAN PADA MATERI CAHAYA DAN ALAT-ALAT OPTIK UNTUK KELAS VIII SMP - Mahayani, Septi; Irwandani, Irwandani; Yuberti, Yuberti; Widayanti, Widayanti (Universitas Tanjungpura, 2018)
AbstractThis research aims to; 1) Determine the feasibility of learning media in the form of a pop-up box based on problem solving as a media for learning physics, 2) to know the attractiveness of learning media in the form of pop-up box based on problem solving as a medium of physics learning. This research is an R & D research that adopts the development of Borg &Gallyang has been modified by Sugiono. Subjects in this study are students class VIII SMPN 5 Bandarlampung, SMP WIYATAMA Bandarlampung and MTS Al-Huda JatiAgung with data collection instruments used in the form of questionnaires given to material experts, media experts, educators physics junior high school to test the quality of media learning and questionnaire response learners to know the interest / response of learners to learning media developed. The type of data generated is qualitative data which is analyzed by guidance criteria of rating category to determine product quality using Likert scale. The results of this study are; 1) Produce a pop-up box product as a learning medium; the product quality that has been developed is